Natural Resources and Conflict: What We Can Do. - Bannon, I; Collier, P (World Bank, 2003)
Violent conflict can be catastrophic for developing countries and their neighbours, stunting and even reversing the course of economic growth. Recent World Bank research on the causes of conflict and civil war finds that the countries most likely to be blighted by conflict are those whose economies depend heavily on natural resources. This book looks at the links between resource dependence conflict and then considers what can be done to help reduce the risk of civil war in these nations. Contributors consider the risks of corruption, secessionist movements, and rebel financing. They also consider the roles played by government, the development community, and the country's population and propose an agenda for global action. Looking at what can be done collectively to diminish the likelihood of civil war, contributors to this volume suggest practical approaches and policies that could be adopted by the international community from financial and resource reporting procedures to commodity tracking systems and enforcement techniques, including sanctions, certification requirements, and aid conditionality.